Influences of Part-Time Jobs in Gaining Workforce Skills Among Psychology Students: Vol. 5, No. 1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In different parts of the country, working while studying has gained popularity during the last several decades. While attending lessons at school, students manage a range of tasks at work. Students who decide to work while they are in school do so for a variety of reasons, including experiences, financial concerns, and a host of other factors. However, this study mainly focused on the influences of part-time jobs in gaining workforce skills among 4th-year psychology students at Bestlink College of the Philippines.The study utilized descriptive quantitative research. The respondents of this research are composed of thirty (30) selected 4th-year psychology working students who used the purposive sampling technique to get the sample needed for this study. The questionnaire used is made up of the Likert scale assessment tool. It contains the demographic profile of the respondents in terms of age, sex, type of job, and number of working hours. Also, it pertains to the factors of doing part-time jobs and indicates the level of workforce skills of the respondents.The summary of findings reveals that the majority of respondents are female and aged from twenty-one to twenty-five (21-25) years old. Additionally, Customer Service ranks first in the most frequent answer of the respondents as their Job Industry. As to number of working hours, twenty-three (23) of the respondents, which is equivalent to seventy-seven percent (77%) of the working students, work for seven to nine (7-9) hours. The findings showed that the main factor of the respondents in doing part-time jobs is work experience. It has the highest average weighted mean, which is three-point forty (3.40), and is verbally interpreted as strongly agree. Furthermore, leadership and problem-solving skills are both the highest level of workforce skills gained by the respondents. It has an average weighted mean of three-point forty-three (3.43), which is verbally interpreted as always.Overall, work experience is the major factor of the respondents in doing part-time jobs. The students may use part-time jobs have experiences which can help them in preparation for their future job. Working part-time also helps in gaining workforce skills, which are beneficial to students. They can use the skills they gained in studying, and also in their future work.
Keywords: Part-time jobs; Workforce skills; Working students